Applying multi-theory model to determine intentions to smoking cessation among male health worker smokers in Kabul, Afghanistan - Mousa Bashir; Farkhondeh Amin Shokravi; Anoshirvan Kazemnejad (Frontiers in Public Health)
IntroductionSmoking causes lung cancer and a wide range of acute and chronic diseases annually throughout the world. A fourth-generation behavioral framework, namely the Multi-Theory Model (MTM) of health behavior change was used to predict the initiation and maintenance of smoking cessation among health worker smokers.MethodsA cross-sectional study of 170 smoking healthcare workers was conducted in Kabul. A non-probability convenience sampling method was used to recruit respondents. A valid and reliable 37-item MTM-based questionnaire was administered to male smokers. Stepwise multiple regression was used to explain smoking cessation. The overall Cronbach’s alpha coefficient (α) for the initial and retention scales of the MTM variables was 0.80 and 0.79, respectively.ResultsThe average age of the participants was 29.33 ± 6.21 years. The reported average year of smoking was 5.6 ± 4.7 with the average number of 5.64 ± 5.21cigarette smoking per day. Behavioral confidence and changes in physical environment were significant predictors of smoking cessation initiation. The sustenance of smoking cessation behavior was significantly influenced by emotional transformation, practicing for change and changes in social environment.ConclusionMTM has the usefulness to assess both the initiation and sustenance behavior of smoking cessation. Potential arrangements utilizing MTM develops ought to be created in future interventions to alter behavior of smoking cessation.